Predicting Car Drivers' Speeding Behavior in Surabaya, Indonesia - Setiawan, Rudy; Prayogo, Michael Antonie (Civil Engineering Dimension, 2025)
This study examines the influence of demographic, psychological, and situational factors on car drivers’ speeding intentions and behaviors in Surabaya, Indonesia, to inform targeted road safety interventions. An online questionnaire yielded 322 valid responses from licensed car drivers with at least six months of driving experience. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) to assess the relationships between driver characteristics, situational factors, speeding intentions, and actual speeding behavior. Favorable road conditions and situational constraints significantly increased speeding intentions, whereas marital status and self-efficacy significantly reduced them. Self-efficacy also directly decreased speeding behavior, and speeding intentions strongly predicted actual speeding. The model explained 36.1% of the variance in speeding intentions and 24.9% in speeding behavior. These findings highlight the need for integrated interventions—combining education, awareness campaigns, and strict enforcement—to address both attitudinal and situational drivers of speeding.